2016
DOI: 10.1590/0103-8478cr20150450
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass traits of goat kids fed high-concentrate diets containing citrus pulp or soybean hulls

Abstract: Performance and carcass traits of goat kids fed high-concentrate diets containing citrus pulp or soybean hulls.Ciência Rural, v.46, n.4, abr, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
5
0
3
Order By: Relevance
“…The replacement of ground corn by by-products in high-concentrate diets generally is done to minimize fluctuation of ruminal pH throughout the day, which may contribute to increase DMI and consequently ADG (Polizel et al, 2016). This study aimed to evaluate the inclusion of WCP as an energetic ingredient in diets for feedlot lambs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The replacement of ground corn by by-products in high-concentrate diets generally is done to minimize fluctuation of ruminal pH throughout the day, which may contribute to increase DMI and consequently ADG (Polizel et al, 2016). This study aimed to evaluate the inclusion of WCP as an energetic ingredient in diets for feedlot lambs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, when 40% of WCP was added, the increase in the NDF may have resulted in a rumen fill limits to feed intake (Waldo, 1986). The increase in NDF of high digestibility in high starch diets normally increase animal performance (Ferreira et al, 2011;Polizel et al, 2016). In addition, the lower DMI for animals fed 40WCP diet may be due to the large water content in the WCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability is thought to derive from the goats’ natural tendency to browse rather than graze, allowing them to adjust their feeding behaviour around food availability 3. This perceived ability, coupled with the lack of high‐quality roughages in some areas of Southern Europe, has led to trials being conducted where goats are offered high‐concentrate rations of up to 85–90 per cent of total dietary intake 4 5. These trials have indicated an improved animal performance (liveweight gain and milk yield), without any significant impacts on goat health, when compared with low‐concentrate rations of up to 30 per cent and poor‐quality roughages 6.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, dietas com alto teor de concentrado são de fácil armazenagem e manejo e proporcionam crescimento rápido e eficiente quando comparado com animais criados em pasto por um mesmo período (Barros et al, 2009). Assim sendo, sistemas intensivos como o confinamento e o uso de dietas com alto teor de concentrado tem se consolidado na produção de cordeiros para abate precoce Ferreira et al, 2014;Gallo et al, 2014;Polizel et al, 2016).…”
Section: Introductionunclassified